A Temperature-Aware Trusted Routing Scheme for Sensor Networks: Security Approach. (March 2022) - Khan, Tayyab; Singh, Karan; Manjul, Manisha; Ahmad, Mohammad Nazir; Zain, Azlan Mohd; Ahmadian, Ali
ABSTRACT: This paper presents a hybrid trust model, and a multifactor, depending on trust value of sensor nodes, remaining energy, and hop count, routing strategy known as Temperature-Aware Trusted Routing Scheme (TTRS). In fact, it establishes the shortest and most trusted routing path. The multifactor strategy selects trustworthy nodes to forward data and reduce energy utilization due to secure shorter routing paths. TTRS incorporates an efficient multifactor hotspot node detection algorithm (HNDA) along with route discovery as well as route maintenance mechanism to detect malicious relay nodes for consistent data delivery in an unattended environment. Experimental results express the admirable average performance gain of TTRS in terms of accurate trust evaluation, network lifetime, packet delivery rate, and average energy consumption per node, as compared to ATRP, EOSR, and SQEER. Consequently, TTRS is more accurate than the aforementioned competitive schemes under different loads in a hostile environment.